2006
DOI: 10.3748/wjg.v12.i6.915
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anaesthesia restores pancreatic microcirculation and decreases the severity of acute pancreatitis

Abstract: To investigate the effect of epidural anaesthesia (EA) on pancreatic microcirculation during acute pancreatitis (AP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 32 publications
2
23
1
Order By: Relevance
“…These findings are in parallel with the literature. 6,24,25 In contrast to some studies from literature, 5,8,9,11 our study showed that the combination of epidural and inhalation anesthesia combination is the ideal anesthesia technique in flap microcirculation. 2,3,6,8 Although there is no statistically significant difference in numbers of rolling, sticking, and transmigrating leukocytes and functional capillary perfusion, this group (group IV) had better flow hemodynamics in the peripheral microcirculation when compared with the inhalation anesthesia group (group I).…”
Section: Discussioncontrasting
confidence: 85%
“…These findings are in parallel with the literature. 6,24,25 In contrast to some studies from literature, 5,8,9,11 our study showed that the combination of epidural and inhalation anesthesia combination is the ideal anesthesia technique in flap microcirculation. 2,3,6,8 Although there is no statistically significant difference in numbers of rolling, sticking, and transmigrating leukocytes and functional capillary perfusion, this group (group IV) had better flow hemodynamics in the peripheral microcirculation when compared with the inhalation anesthesia group (group I).…”
Section: Discussioncontrasting
confidence: 85%
“…Park et al found recently, when comparing arterial lactate levels in patients undergoing total knee arthroplasty having sevoflurane or spinal anesthesia, a higher lactate increase during sevoflurane anesthesia, thus suggesting a lower production of ischemic metabolites in the spinal anesthesia group [ 32 ]. Improved microcirculation during organ inflammation has been indicated in an experimental rat model using epidural anesthesia [ 33 ]. A positive effect on the tissue perfusion by neuraxial block may modulate the inflammatory response during ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Demirag et al [ 23 ] showed for the first time the benefit of TEA on the severity of AP in rats. The authors evaluated the impact of TEA during AP by measuring the pancreatic microcirculatory flow and arterial blood gases, and completed the experiment with histological analyses to investigate the development of pancreatic necrosis.…”
Section: Introductionmentioning
confidence: 99%